2021
DOI: 10.3390/cells10071841
|View full text |Cite
|
Sign up to set email alerts
|

Indonesia-Based Study of the Clinical and Cost-Saving Benefits of Subcutaneous Allergen Immunotherapy for Children with Allergic Rhinitis in Private Practice

Abstract: Background: Until now, the cost of allergy treatment in the insured public health care system and the non-insured self-financing private health care system in Indonesia has not been well documented and published, as well as the cost of allergy treatment with subcutaneous immunotherapy. Objective: To evaluate the clinical and cost benefits of allergic rhinitis treatment in children with subcutaneous immunotherapy in a non-insured self-financing private health care system. Methods: A retrospective cohort study c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…AIT can be performed by subcutaneous (SCIT) or sublingual (SLIT), and growing evidences proved that SCIT was better than SLIT in controlling allergic symptoms, improving compliance and reducing rescue medication consumption (13,14). Although SCIT is a suitable treatment for pediatric AR, not all children respond to this therapy, and the efficacy always fluctuates across users (15)(16)(17). Therefore, to identify and validate potentially important laboratory predictors for SCIT response may play a pivotal role on SCIT treatment for pediatric AR patients.…”
Section: Introductionmentioning
confidence: 99%
“…AIT can be performed by subcutaneous (SCIT) or sublingual (SLIT), and growing evidences proved that SCIT was better than SLIT in controlling allergic symptoms, improving compliance and reducing rescue medication consumption (13,14). Although SCIT is a suitable treatment for pediatric AR, not all children respond to this therapy, and the efficacy always fluctuates across users (15)(16)(17). Therefore, to identify and validate potentially important laboratory predictors for SCIT response may play a pivotal role on SCIT treatment for pediatric AR patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing evidence showed that SCIT was more effective than SLIT in reducing allergic symptoms, especially in pediatric AR ( 13 15 ). Although SCIT is more effective and compliant, this treatment is not successful for every child who has AR, and the outcome fluctuates among the different users ( 9 , 16 ). Besides, the treatment process of SCIT takes over 3 years, but a reliable method or biomarker to predict the treatment response is absent.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] However, there still were some patients who did not respond well to SCIT, and AR children were at higher risk of adverse reactions during SCIT. [15][16][17] Therefore, a trustworthy biomarker to predict the clinical efficacy of SCIT was crucial. 18 Although previous publications discovered that IgG4 antibodies, serum periostin, and specific IgE/total-IgE ratio were associated with SCIT responses and contributed to the immune tolerance formation.…”
Section: Introductionmentioning
confidence: 99%